2021
DOI: 10.1016/j.cjco.2020.09.020
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Arterial Thrombosis in a 78-Year-Old Patient: Catastrophic Thrombotic Syndrome in COVID-19

Abstract: We describe a patient with COVID-19 and multiple concomitant thromboses occurring on the 9th day of hospital stay. Thromboses were found in distinct zones of the aorta as well as in the renal, humeral and pulmonary arteries. The extensive biological workup performed following this catastrophic thrombotic syndrome found no evidence for underlying prothrombotic disease. In light of current evidence regarding endothelium abnormalities related to COVID-19, this extreme case of catastrophic thrombotic syndrome sugg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…They can be fatal due to sudden obstruction of microcirculation, leading to stroke or cardiac death. However, AT is associated in severe COVID-19 cases even in the absence of atherosclerosis or plaque rapture [69] , [70] , [71] ; COVID-19 instigated excessive endothelial activation has been linked to AT in regions such as the aorta, renal, and peripheral arteries [72] . Literature review suggests AT occurs in about 2.2% to 8.8% of seriously affected COVID-19 patients [35] , with thrombosis observed in the superior mesenteric artery (8%), coronary arteries (5% to 9%), great vessels (aorta, common iliac, common carotids, and brachiocephalic artery; 14% to 19%), cerebral arteries (18% to 24%) and limb arteries (24% to 39%) [35] , [73] .…”
Section: Overview Of the Pathophysiology Of Thrombosismentioning
confidence: 99%
“…They can be fatal due to sudden obstruction of microcirculation, leading to stroke or cardiac death. However, AT is associated in severe COVID-19 cases even in the absence of atherosclerosis or plaque rapture [69] , [70] , [71] ; COVID-19 instigated excessive endothelial activation has been linked to AT in regions such as the aorta, renal, and peripheral arteries [72] . Literature review suggests AT occurs in about 2.2% to 8.8% of seriously affected COVID-19 patients [35] , with thrombosis observed in the superior mesenteric artery (8%), coronary arteries (5% to 9%), great vessels (aorta, common iliac, common carotids, and brachiocephalic artery; 14% to 19%), cerebral arteries (18% to 24%) and limb arteries (24% to 39%) [35] , [73] .…”
Section: Overview Of the Pathophysiology Of Thrombosismentioning
confidence: 99%
“…A total of 55 patients from the database research and 1 patient from our facility were included. 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 Of the included studies, 12 were case series and 26 were case reports. Essential characteristics of the included patients are outlined in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Both unilateral and bilateral thromboses have been reported. Moreover, clinical practice has shown that renal artery thrombosis may also occur concomitantly with other thrombotic complications in the body, such as pulmonary embolism and thrombosis in different body zones, such as the heart, aorta, limbs, and brain [21 , 25 , 26] . The majority of the aforementioned cases were strongly correlated with COVID-19-induced thrombosis because the diagnosis was demonstrated by reverse-transcriptase polymerase chain reaction test results, chest imaging findings (eg, ground-glass opacities), and a relatively high D-dimer level.…”
Section: Discussionmentioning
confidence: 99%